2012
DOI: 10.1245/s10434-011-2194-1
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 Promotes Cell Growth and Metastasis Through Repression of p16ink4a in Colorectal Cancer

Abstract: UHRF1 expression is upregulated in CRC and is associated with the progression of CRC. Moreover, RNAi of UHRF1 decreases proliferation and migration but enhances apoptosis of CRC cells, with increased p16(ink4a) expression. UHRF1 promotes CRC growth and metastasis, likely by repressing p16(ink4a), and thus it may be used as a biomarker or even a therapeutic target for CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
117
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(122 citation statements)
references
References 26 publications
5
117
0
Order By: Relevance
“…At the M phase of the cell cycle, USP7 disassociates from UHRF1, thus exposing UHRF1 to proteasomal degradation (18). Importantly, manipulating the UHRF1 level in cells has been shown to affect cell proliferation (11,18,20). Collectively, these findings suggest that maintaining an appropriate level of UHRF1 is important for processes such as cell proliferation regulation and the DDR.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…At the M phase of the cell cycle, USP7 disassociates from UHRF1, thus exposing UHRF1 to proteasomal degradation (18). Importantly, manipulating the UHRF1 level in cells has been shown to affect cell proliferation (11,18,20). Collectively, these findings suggest that maintaining an appropriate level of UHRF1 is important for processes such as cell proliferation regulation and the DDR.…”
mentioning
confidence: 89%
“…These domains underlie the ability of UHRF1 to play a role in multiple processes, such as maintenance of DNA methylation, heterochromatin organization, and gene transcription (1)(2)(3)(4)(5)(6)(7)(8). Previous studies identified a correlation between UHRF1 overexpression and cancer progression and metastasis, possibly through silencing of various tumor suppressor genes (9)(10)(11)(12). Moreover, UHRF1 is implicated in apoptosis in response to DNA damage.…”
mentioning
confidence: 99%
“…[18][19][20] Its downregulation arrested colorectal cancer cells at G0/G1 phase by reducing the levels of cyclins A and D1, and induced p16 INK4A -mediated apoptosis. 21 UHRF1 silencing arrested gall bladder cancer cells at G1/S phase in a p21-dependent pathway and triggered apoptosis by upregulating the expression of promyelocytic leukemia (PML) protein. 22 BALB/c nude mice injected with UHRF1 silenced gastric cancer cells (MKN45-shUHRF1 cells) produced smaller tumors and showed decrease in Ki-67 antigen, the marker of cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we saw that also Wang et al 71 show that UHRF1 is upregulated in colorectal cancer case and facilitates in cell proliferation and metastasis via suppression of p16 nk4 . It is evident that overexpression of CDCA2 leads to repression of p16 nk4 and cell proliferation.…”
Section: Dicationmentioning
confidence: 67%
“…This interaction is basically the inhibition of the degradation of UHRF1. Wang et al 71 also show that UHRF1 is upregulated in colorectal cancer case and facilitates in cell proliferation and metastasis via suppression of p16 nk4 . Similar findings have been made in 72 , 73 & 74 .…”
Section: Dicationmentioning
confidence: 94%